2019
DOI: 10.1080/1828051x.2019.1645623
|View full text |Cite
|
Sign up to set email alerts
|

Monensin controlled-release capsule administered in late-pregnancy differentially affects rumination patterns, metabolic status, and cheese-making properties of the milk in primiparous and multiparous cows

Abstract: 2019) Monensin controlled-release capsule administered in late-pregnancy differentially affects rumination patterns, metabolic status, and cheese-making properties of the milk in primiparous and multiparous cows, ABSTRACTThe increased resistance to disease observed after monensin treatment could reflect a reduction of inflammation and oxidative stress. We hypothesised that if monensin supplementation was given before calving, it would help in controlling inflammation, reduce the susceptibility to disease and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 32 publications
(46 reference statements)
2
23
1
Order By: Relevance
“…In particular, the increase at lambing time proved to be less pronounced and less prolonged in MUP ewes than in PRP ewes. These data support the presence of an exacerbated immunity challenge in younger ewes around lambing time, as was observed previously in cattle (Mezzetti et al, 2019).…”
Section: Inflammationsupporting
confidence: 92%
“…In particular, the increase at lambing time proved to be less pronounced and less prolonged in MUP ewes than in PRP ewes. These data support the presence of an exacerbated immunity challenge in younger ewes around lambing time, as was observed previously in cattle (Mezzetti et al, 2019).…”
Section: Inflammationsupporting
confidence: 92%
“…These positive effect of monensin on rumen fermentation is reflected by trends of several plasma analytes (i.e reduced BHB and NEFA concentrations and higher plasma glucose) in cows treated with monensin [120,121,123]. A recent study [124,125] found reduced infiltration of T and B leukocytes in the rumen fluid from transition dairy cows that received a controlled-release capsule of monensin 21 days before the expected calving date (expected release rate, 335 mg/d for 95 days). Such an outcome suggests monensin promotes the stabilization of rumen milieu, probably through mitigating pH alterations related to the adaptation of dairy cows to the lactation diet.…”
Section: Nutritional Strategies and Modulatory Treatments To Improve ...mentioning
confidence: 99%
“…The decrease in non-esterified fatty acids after 2 weeks may be due to the increase in dry matter intake (10,17), and this low level of NEFA may also be associated with a negative energy balance that resulted from increasing metabolic requirements after calving (2,16,32). The observed decreases in plasma NEFA levels in this study might be related to changes in adipose tissue density in response to the administration of a monensin CRC before calving (19,24). Grummer et al (12) reported that the lower NEFA concentration indicates less fat mobilization in these cows.…”
Section: Resultsmentioning
confidence: 60%
“…In our study, the highest level of urea in cows that received a monensin CRC was found 1 week after calving, and this value was higher than in the other weeks (P ˂ 0.05). The urea concentration in group M was increased 1 week after parturition compared to that in group C. The higher uremia detected in blood suggests that the monensin CRC could have increased the role of amino acids from muscle tissue in covering the energy deficit during a NEB because blood urea is partially derived from the deamination of muscle amino acids after they have been used as gluconeogenic sources (24).…”
Section: Resultsmentioning
confidence: 92%